Accelerated long‐range corrected exchange functional using a two‐gaussian operator combined with one‐parameter progressive correlation functional [LC‐BOP(2Gau)]. Issue 1 (19th November 2018) - Song, Jong‐Won; Hirao, Kimihiko
Abstract : Recently, we proposed a simple yet efficient method for the computation of a long‐range corrected (LC) hybrid scheme [LC‐DFT(2Gau)], which uses a modified two‐Gaussian attenuating operator instead of the error function for the long‐range HF exchange integral. This method dramatically reduced the computational time while maintaining the improved features of the LC density functional theory (DFT). Here, we combined an LC hybrid scheme using a two‐Gaussian attenuating operator with one‐parameter progressive correlation functional and Becke88 exchange functional with varying range‐separation parameter values [LC‐BOP(2Gau) with various μ values of 0.16, 0.2, 0.25, 0.3, 0.35, 0.4, and 0.42] and demonstrated that LC‐BOP(2Gau) reproduces well the thermochemical and frontier orbital energies of LC‐BOP. Additionally, we revised the scaling factors of the Gaussian multipole screening scheme for LC‐DFT(2Gau) to correspond to the angular momentum of orbitals, which decreased the energy deviations from the energy with the no‐screening scheme. © 2018 Wiley Periodicals, Inc. Abstract : The authors proposed a simple yet efficient method for the computation of a long‐range corrected (LC) hybrid scheme [LC‐DFT(2Gau)], which uses a modified two‐Gaussian attenuating operator instead of the error function for the long‐range HF exchange integral. This method dramatically reduced the computational time while maintaining the improved features of the LC density functional theory. The authors combined an LC scheme using a two‐Gaussian attenuating operator with OP correlation functional and Becke88 exchange functional with varying range‐separation parameter values [LC‐BOP(2Gau) with μ = 0.16–0.42] and demonstrated that LC‐BOP(2Gau) reproduces well the thermochemical and frontier orbital energies of LC‐BOP.